1999
DOI: 10.1139/gen-42-3-420
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in <i>Elymus caninus</i> as revealed by isozyme, RAPD, and microsatellite markers

Abstract: Genetic diversity of 33 Elymus caninus accessions was investigated using isozyme, RAPD, and microsatellite markers. The three assays differed in the amount of polymorphism detected. Microsatellites detected the highest polymorphism. Six microsatellite primer pairs generated a total of 74 polymorphic bands (alleles), with an average of 15.7 bands per primer pair. Three genetic similarity matrices were estimated based on band presence or absence. Genetic diversity trees (dendrograms) were derived from each marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 0 publications
5
36
0
Order By: Relevance
“…Similarly, higher genetic diversity was observed for microsatellite loci (A = 4.07; H E = 0.50) than for allozyme loci (A = 1.53; H E = 0.20) in a perennial species (Freville et al 2001). This tendency was also evident in many other plant species (Powell et al 1996;Streiff et al 1998;Sun et al 1999;Guadagnuolo et al 2001). Therefore, the higher level of polymorphism associated with SSR is to be expected partly because of the unique mechanism responsible for generating SSR allelic diversity by replication slippage (Powell et al 1996), and partly because of the limited number of polymorphic loci and representation of only variation in the coding regions for the allozyme loci (Guadagnuolo et al 2001).…”
Section: Cluster Analysismentioning
confidence: 63%
“…Similarly, higher genetic diversity was observed for microsatellite loci (A = 4.07; H E = 0.50) than for allozyme loci (A = 1.53; H E = 0.20) in a perennial species (Freville et al 2001). This tendency was also evident in many other plant species (Powell et al 1996;Streiff et al 1998;Sun et al 1999;Guadagnuolo et al 2001). Therefore, the higher level of polymorphism associated with SSR is to be expected partly because of the unique mechanism responsible for generating SSR allelic diversity by replication slippage (Powell et al 1996), and partly because of the limited number of polymorphic loci and representation of only variation in the coding regions for the allozyme loci (Guadagnuolo et al 2001).…”
Section: Cluster Analysismentioning
confidence: 63%
“…Microsatellite loci are a demonstrated rich source of highly polymorphic genetic markers in an ever-increasing number of organisms, and are promising markers for the detection of genetic variation in species, while allozyme analysis has revealed only low levels of variation (Saghai-Maroof et al 1994;Terauchi and Konuma 1994;Lehmann et al 1996;Sanchez et al 1996;Estoup et al 1998;Meglecz et al 1998;Streiff et al 1998;Dje et al 1999;Sun et al 1999;Lemaire et al 2000). For example, in the yam (Dioscorea tokoro), Terauchi and Konuma (1994) found that microsatellites show higher levels of genetic variability than allozymes with respect to heterozygosity.…”
Section: Discussionmentioning
confidence: 99%
“…These results further suggest that microsatellite loci are more effective in detecting small genetic differences among populations than are allozyme loci. These differences in the nature of allozyme vs microsatellite loci would affect variation at different levels of genetic variation between these two kinds of markers (Clegg 1989;Smith et al 1992;Sun et al 1998Sun et al , 1999. Population genetic structure based on microsatellite and allozyme data analysis…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that microsatellite markers are a very useful tool for the analysis of genetic diversity in Elymus species (Sun et al 1998c(Sun et al , 1999(Sun et al , 2001(Sun et al , 2002. Within the Elymus genus, several microsatellite markers have been developed from genomic DNA libraries from E. caninus L. and E. alaskanus (Scrib.…”
Section: Introductionmentioning
confidence: 99%